Short Ragweed Pollen Triggers Allergic Inflammation via TLR4-dependent TSLP/OX40L/OX40 Signaling Pathways - Li, De-Quan (2011)
BACKGROUND: Allergic diseases affect large population. Pollen, a ubiquitous allergen, is the trigger of seasonal rhinitis, conjunctivitis and asthma, as well as an exacerbating factor of atopic dermatitis. However, the underlying mechanism by which pollen induces thymic stromal lymphopoietin (TSLP) triggered allergic inflammation via epithelial innate immunity is largely unknown. OBJECTIVE: To explore whether short ragweed (SRW) pollen induces TSLP/OX40L/OX40 signaling via Toll-like receptor (TLR) 4-dependent pathways in allergic disease. METHODS: Three models were used for this study, a well-characterized murine model of allergic conjunctivitis induced by SRW pollen, a topical challenge model on mouse ocular surface, and a culture model of primary human corneal epithelium exposed to aqueous extract of defatted SRW pollen (SRWe). RESULTS: The topical challenges with SRW pollen generated a typical allergic conjunctivitis in BALB/c mice. Clinical signs, stimulated TSLP/OX40L/OX40 signaling and Th2 cytokines in ocular mucosa and draining cervical lymph nodes were significantly reduced or eliminated in TLR4 deficient (Tlr4-d) or MyD88 knockout (MyD88(−/−)) mice, compared with their wild type littermates. SRWe stimulated TSLP production by ocular epithelia in wild type, but not Tlr4-d or MyD88(−/−) mice. SRWe stimulated TSLP was blocked by TLR4 antibody and NF-kB inhibitor in mouse and human corneal epithelia. CONCLUSION: We for the first time uncovered a novel phenomenon that SRW pollen, acting as a functional TLR4 agonist, initiates TLR4-dependent TSLP/OX40L/OX40 signaling that triggers Th2-dominant allergic inflammation. These findings shed light on the understanding of mucosal epithelial innate immunity, and create new therapeutic targets to cure allergic diseases.